Attitudes towards exercise content on social media and the choice of fitness trainer - Alerić, Nikolina; Penjak, Ana; Karninčić, Hrvoje (Annales Kinesiologiae, 2023)
The aim of this study was to: a) investigate and determine gender differences towards factors influencing gym-goers’ choice of fitness trainer; and b) to identify and explain gender differences in gym-goers’ attitudes towards social media exercise contents (SMEC). For this purpose, a questionnaire was created. The study was conducted on a sample of 50 gym-goers (N1=13 male and N2=37 female), all attending a gym in Split, Croatia. The variable sample consisted of five groups of variables. Test-retest overlap was performed to determine the reliability (88.20%) of the questionnaire. The results showed that the affirmative attitudes were statistically significant in contrast to the non-affirmative attitudes (Wilcoxon Matched Pairs Test, T=250.00, Z=3.60, p<0.001). In addition, male gym-goers generally have a significantly more affirmative attitude towards SMEC than female gym-goers (Mann-Whitney U-test, U=119.50, Z=–2.68, p=0.007). Furthermore, there are gender differences in choosing a fitness trainer based on their appearance; but there are no gender differences in the attitude towards the number of fitness trainers’ followers on social media as an indicator of trustworthiness. As this study was specifically concerned with the attitudes of gym-goers, future studies should focus on sports professionals and their attitudes toward this topic.